Short-Selling and Financial Performance of SMEs in China: The Mediating Role of CSR Performance - Wenzhen Mai; Nik Intan Norhan binti Abdul Hamid (International Journal of Financial Studies, 2021)
The aim of this study is to examine the effect of short-selling deregulation on the financial performance of SMEs in China. The external governance role of short-selling is also tested by adopting corporate social responsibility (CSR) performance as the mediating effect. This study investigates a panel data analysis with a sample of 5038 firm-years of SMEs listed in Shenzhen Stock Exchange from 2010 to 2019. The PSM-DID method is adopted in this study to alleviate self-selection and endogenous problems to observe the comparable pure effect of short-selling deregulation, while the mediation test is conducted based on Baron and Kenny’s model. The finding of this study showed that the existence of short-selling could enhance firm financial performance and the mediating effect of CSR performance position in their relationship. In addition, the further analysis revealed that the mediating effect of CSR is more pronounced for family businesses and firms with high real short-selling threats. The robust test of alternative measurements is conducted and valid. This study provides insights for policymakers to consider further short-selling ban lifting and corporate executives to practice more CSR activities to improve the financial performance. Limitations and further implications of this study are also discussed.